Change in activity participation of mental health care users with major depressive disorder attending occupational therapy groups - Meyer, Annalie Francina (My University, 2020)
Introduction: Activity participation of mental health care users (MHCUs) with major depressive disorders (MDD) is usually severely affected and prevents them to answer to everyday demands of life. Little is known about the activity participation of MHCUs with MDD attending occupational therapy groups. This study aimed to describe activity participation of MHCUs with MDD attending occupational therapy group sessions at a private psychiatric hospital and to determine the relationship between activity participation domains and MDD as perceived by the MHCUs. Methodology: A quasi-experimental, longitudinal, pre-post group study design was employed to collect data from a sample of 70 MHCUs with MDD. The measures in this study were the Activity Participation Outcome Measure (APOM) and the Patient Health Questionnaire 9 (PHQ-9). Results: The findings of this study indicate a significant improvement in activity participation from baseline to discharge across all the domains of the APOM. The total number of groups attended by participants tested was superior to length of stay when correlated with improvement in APOM scores. The findings of the study demonstrated a non-significant, negligible correlation between activity participation and perceived depression as measured by the PHQ-9.Discussion: Occupational therapy groups play a valuable and integral role in the road to recovery for MHCUs with MDD admitted to a private psychiatric setting. Insignificant correlations between PHQ-9 and APOM scores suggest that future research in using the PHQ-9 as an outcome measure in acute mental health settings is needed
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy, 2020